Analysis of Mathematical Problem-Solving Abillity of Fifth Grade Studenst of MI Darus Sholeh Reviewed from the Level of Self- Confidence - Muhhamad Khaiz Al Mubarok; Ifa Seftia Rakhma Widiyanti; Wendri Wiratsiwi (Universitas Sriwijaya in Collaboration with HDPGSDI (Himpunan Dosen PGSD Indonesia), 2026)
Self-confidence is one of the affective factors that influences students’ success in learning mathematics. Low self-confidence causes students to be less active, hesitant in expressing opinions, and to experience difficulties in solving mathematical problems. This study aims to analyze the effect of self-confidence on the mathematical ability of fifth-grade students at MI Darus Sholeh. This research used a quantitative approach with a survey method. The research subjects were fifth-grade students of MI Darus Sholeh. Data collection techniques were carried out using a self-confidence questionnaire and a mathematical ability test which included indicators of understanding the problem, planning the solution, implementing the plan, and interpreting the results. The data were analyzed using simple regression analysis to determine the effect of self-confidence on students’ mathematical ability. The results showed that self-confidence had a positive effect on students’ mathematical ability. Students with high levels of self-confidence tended to be more active, willing to try, and able to solve mathematical problems well. Conversely, students with low self-confidence experienced difficulties in understanding concepts and solving problems. These findings indicate that improving self-confidence is an important factor in enhancing students’ mathematical ability.